Types of Code-Switching Found in The Friday Podcast - I Ketut Juliana Damara Putra; I Gde Agoes Caskara Surya Putra (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2024)
The objective of this study is to know the various types of code switching found in The Friday Podcast, especially in episode 213. Descriptive qualitative method is used to analyse the data. This study analyzed the different types of code switching using Appel & Muysken theory of Bilingualism, as presented in their book entitled Language Contact and Bilingualism (1987). There are three types of code switching stated by Appel & Muysken. The findings of this study revealed that all three types of Code Switching were discovered in The Friday Podcast. Intra-Sentential switching is the most common sort of code-switching occurrence in The Friday Podcast. Meanwhile, Intersentential-Switching is the speaker's least dominant data. For the conclusion, the reason why intrasentential-switching got the most occurrences in this podcast because the audience of this podcast is Indonesian people who are the majority of it not really fluent in English. The speakers in this podcast also using the familiar English terms that Indonesian society frequently heard.